Gamma radiolytic stability of the novel modified diglycolamide 2, 2′-oxybis(N, N-didecylpropanamide) (mTDDGA) for grouped actinide extraction. Issue 20 (25th April 2022) - Verlinden, Bart; Van Hecke, Karen; Wilden, Andreas; Hupert, Michelle; Santiago-Schübel, Beatrix; Egberink, Richard J. M.; Verboom, Willem; Kowalski, Piotr M.; Modolo, Giuseppe; Verwerft, Marc; Binnemans, Koen; Cardinaels, Thomas
Abstract : The radiolysis behavior of a new diglycolamide for solvent extraction of actinides and lanthanides was studied. The observed degradation rate was lower than for the reference molecule and 22 degradation compounds were identified. Abstract : Reprocessing of spent nuclear fuel aims at improving resource efficiency and reducing its radiotoxicity and heat production in the long term. The necessary separation of certain metal ions from the spent fuel solutions can be achieved using different solvent extraction processes. For the scenario of the EURO-GANEX process, the use of the new, modified diglycolamide 2, 2′-oxybis( N, N -didecylpropanamide) (mTDDGA) was recently proposed to simplify the current solvent composition and reduce extraction of fission products. Before further developing the process based on this new ligand, its stability under ionizing radiation conditions needs to be studied. For this reason, gamma irradiation experiments were conducted followed by analyses with high performance liquid chromatography coupled to a mass spectrometer (HPLC-MS). The determined degradation rate of mTDDGA was found to be lower than that of the reference molecule N, N, N ′, N ′-tetra- n -octyl-diglycolamide (TODGA). Many identified degradation compounds of both molecules are analogues showing the same bond breaking, although also unreported de-methylation, double/triple de-alkylation and n -dodecane addition products were observed.